2015
DOI: 10.1038/mt.2015.93
|View full text |Cite
|
Sign up to set email alerts
|

S100A1 DNA-based Inotropic Therapy Protects Against Proarrhythmogenic Ryanodine Receptor 2 Dysfunction

Abstract: Restoring expression levels of the EF-hand calcium (Ca(2+)) sensor protein S100A1 has emerged as a key factor in reconstituting normal Ca(2+) handling in failing myocardium. Improved sarcoplasmic reticulum (SR) function with enhanced Ca(2+) resequestration appears critical for S100A1's cyclic adenosine monophosphate-independent inotropic effects but raises concerns about potential diastolic SR Ca(2+) leakage that might trigger fatal arrhythmias. This study shows for the first time a diminished interaction betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 44 publications
6
25
0
Order By: Relevance
“…2A). In addition, further evidence of a physical interaction between RyR2 and S100A1 has been recently provided via proximity ligation assays and immunoprecipitation (6).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2A). In addition, further evidence of a physical interaction between RyR2 and S100A1 has been recently provided via proximity ligation assays and immunoprecipitation (6).…”
Section: Discussionmentioning
confidence: 99%
“…Either way, these results require both S100A1 and CaM to concurrently bind to RyR2. Numerous studies in electrically stimulated and quiescent cardiomyocytes have indicated that S100A1 indeed has a dual effect on the activity of the macromolecular RyR2 complex by improving both systolic opening and diastolic closure of the channel when intracellular S100A1 protein levels are elevated above normal (4,6,25). Increasing the amount of S100A1 bound to the RyR2 significantly reduced the calcium spark rate in normal cardiomyocytes and rescued the arrhythmogenic diastolic RyR2 dysfunction in failing cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations